High-strength PBS biodegradable plastic and preparation method thereof

By using specific functional additives and catalysts in the preparation of PBS biodegradable plastics, the brittleness, strength, crystallization speed and degradation speed of PBS plastics in processing and application are solved, and high strength, rapid crystallization and good heat resistance are achieved. and the effect of prolonging degradation time.

CN119391147APending Publication Date: 2025-02-07SHANDONG RUIAN BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411517824.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In actual processing and application, existing PBS biodegradable plastics have problems such as high brittleness, low strength, slow crystallization speed, insufficient heat resistance and excessive degradation speed.

Method used

High-strength PBS biodegradable plastics are prepared by selecting specific functional additives and catalysts to match them with raw materials. The specific method includes adding functional additives such as polyethylene wax and oxidizing polyethylene wax to the esterification reaction, and using titanate catalysts and acetic alkaline substances as catalysts to increase the crystallization temperature of PBS plastics and speed up the crystallization speed. Enhance tensile strength and high temperature resistance while extending degradation time.

Benefits of technology

It realizes high strength, rapid crystallization, good heat resistance and extended degradation time of PBS plastic, which improves its performance and durability in practical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391147A_ABST
    Figure CN119391147A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a high-strength PBS biodegradable plastic and a preparation method thereof.The high-strength PBS biodegradable plastic is prepared from 4000-5000 parts of succinic acid, 5000-6000 parts of 1, 4-butanediol, 0.9-22 parts of a first catalyst and 4.5-550 parts of a functional additive; wherein the functional aids comprise a first functional aid and a second functional aid; the first functional additive comprises at least one of polyethylene wax, polypropylene wax and oxidized polyethylene wax; the second functional additive is selected from one of a formula (I) or a formula (II); the weight ratio of the first functional additive to the second functional additive is (0.5-3): 1; according to the high-strength PBS biodegradable plastic prepared by selecting a specific functional aid and a catalyst to be matched with the raw materials, the crystallization temperature of the PBS plastic is increased, the crystallization speed is increased, meanwhile, the tensile strength and the high-temperature resistance of the PBS plastic are improved, the hydrophobicity of the PBS plastic is enhanced, and therefore the degradation time of the PBS plastic is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer materials, and in particular to a high-strength PBS biodegradable plastic and a preparation method thereof. Background Art

[0002] Biodegradable plastics refer to a type of plastic that is degraded by microorganisms such as bacteria, molds (fungi) and algae that exist in nature. An ideal biodegradable plastic is a polymer material that has excellent performance, can be completely decomposed by environmental microorganisms after being discarded, and is eventually inorganicized to become a component of the carbon cycle in nature. "Paper" is a typical biodegradable material, while "synthetic plastics" are typical polymer materials. Therefore, biodegradable plastics are polymer materials that have the properties of both "paper" and "synthetic plastics". The market size of biodegradable plastics is rapidly expanding, especially in the catering industry, where products need to have a certain degree of heat resistance, but some conventional biodegradable materials on the market currently lack heat resistance.

[0003] PBS (polybutylene succinate) resin is a biodegradable aliphatic polyester material with good toughness, good thermal stability, high crystallinity and good heat resistance. It is widely used in disposable tableware, lunch boxes, straws, cups, disposable shopping bags, agricultural films and other fields.

[0004] However, in actual processing and application, PBS resin is relatively brittle and has low strength, which limits its application range. At the same time, the crystallization rate of PBS resin is relatively slow, resulting in low production efficiency during the processing and easily affecting product performance. In addition, the excessively fast degradation rate of PBS resin is not what the industry expects. Summary of the invention

[0005] The present application aims to overcome at least one of the defects of the prior art and provide a high-strength PBS biodegradable plastic and a preparation method thereof. The high-strength PBS biodegradable plastic is prepared by selecting specific functional additives and catalysts to match the raw materials. While increasing the crystallization temperature of the PBS plastic and accelerating the crystallization rate, the tensile strength and high temperature resistance of the PBS plastic are improved, and the hydrophobicity of the PBS plastic is enhanced, thereby extending the degradation time of the PBS plastic.

[0006] In a first aspect, the present application provides a high-strength PBS biodegradable plastic, which is achieved through the following technical solutions:

[0007] A high-strength PBS biodegradable plastic comprises the following raw materials in parts by weight:

[0008] 4000-5000 parts of succinic acid, 5000-6000 parts of 1,4-butanediol, 0.9-22 parts of the first catalyst, and 4.5-550 parts of a functional additive;

[0009] Wherein, the functional auxiliary agent includes a first functional auxiliary agent and a second functional auxiliary agent;

[0010] The first functional additive includes at least one of polyethylene wax, polypropylene wax, and oxidized polyethylene wax;

[0011] The second functional auxiliary agent is selected from one of formula (I) or formula (II);

[0012]

[0013] In formula (I), n is a positive integer selected from 1 to 9;

[0014]

[0015]

[0016] In formula (II), m is a positive integer selected from 1 to 9;

[0017] The weight ratio of the first functional auxiliary agent to the second functional auxiliary agent is (0.5-3):1.

[0018] A high-strength PBS biodegradable plastic according to an embodiment of the present application has at least the following beneficial effects:

[0019] The high-strength PBS biodegradable plastic of the present application introduces a first functional additive and a second functional additive. The first functional additive has the effects of lubrication and heterogeneous nucleation, can control the crystal morphology, and also avoids the problem of reduced toughness and crystallinity caused by increased crosslinking degree of the system. The second functional additive introduces a side chain long-chain alkyl while strengthening branching and crosslinking in the polymerization process. On the one hand, the additional long chain of the first functional additive is matched with the side chain long-chain alkyl of the second functional additive to increase the crystallization temperature of the PBS plastic, accelerate the crystallization speed, have good processability, and at the same time improve the tensile strength and high temperature resistance of the PBS plastic; on the other hand, the introduction of the long-chain alkyl can improve the hydrophobicity of the PBS plastic, reduce the attachment of biological bacteria, and reduce the release of biodegradable enzymes, thereby extending the degradation time of the PBS plastic and making it more durable.

[0020] During the esterification process of PBS, 1,4-butanediol is easily cyclized to tetrahydrofuran, which will increase the side reactions in the production process and reduce the reaction efficiency. If the side reaction of tetrahydrofuran cyclization is serious, it will also affect the vacuum degree of the polymerization reaction, thereby affecting the performance of PBS and easily causing environmental pollution. The introduction of long-chain alkyl in the second functional additive can spatially hinder the cyclization reaction of tetrahydrofuran, improve the synthesis efficiency of PBS plastics, and enhance the comprehensive performance of PBS plastics.

[0021] The weight ratio of succinic acid and 1,4-butanediol in the present application can control the usage of 1,4-butanediol, reduce the alcohol-acid molar ratio, facilitate the full reaction, improve the utilization rate of raw materials, reduce the occurrence of tetrahydrofuran cyclization reaction, and improve the reaction efficiency.

[0022] According to some embodiments of the present application, the weight ratio of the first functional auxiliary agent to the second functional auxiliary agent is (2-3): 1. This ratio can further improve the heat resistance and crystallization performance while improving the crystallinity of PBS.

[0023] According to some embodiments of the present application, the first catalyst includes at least one of a titanate catalyst and a germanium catalyst.

[0024] Furthermore, the first catalyst includes at least one of tetrabutyl titanate and germanium dioxide. Tetrabutyl titanate exhibits high catalytic activity in the synthesis of PBS, and the product has a large molecular weight and is pollution-free. Germanium dioxide has good stability and mild reaction, and can promote the synthesis efficiency of PBS.

[0025] According to some embodiments of the present application, the prepared raw material further includes 1-10 parts by weight of a second catalyst.

[0026] Furthermore, the second catalyst includes at least one of hexabutylguanidine acetate, tetramethyl dibutylguanidine acetate, trimethylamine, and tetrahydropyridine. Hexabutylguanidine acetate and tetramethyl dibutylguanidine acetate can effectively reduce the activation energy of the esterification reaction, thereby accelerating the reaction, improving the yield of the esterification reaction, improving the selectivity and purity of the target product, and the reaction conditions are mild, which conforms to the principles of green chemistry; alkaline substances such as hexabutylguanidine acetate and tetramethyl dibutylguanidine acetate can also reduce the cyclization reaction and improve the performance of PBS plastics. Trimethylamine and tetrahydropyridine have high catalytic activity, can promote the reaction at lower temperature and pressure, have stable catalytic effect, are not easy to deactivate, and can maintain catalytic activity for a long time.

[0027] According to some embodiments of the present application, the preparation of the compound of formula (I) comprises the following steps:

[0028] A straight-chain alkyl acid and glycerol are mixed in a molar ratio of 1:1, and then 1% by weight of p-toluenesulfonic acid and 0.5% by weight of toluene are added, and the reaction is carried out under nitrogen protection. The temperature of the oil bath is adjusted to 130° C., and the reaction is refluxed for 10 hours with continuous stirring. When the acid value of the reaction system reaches a stable state and no longer changes, the reaction product is taken out, washed with a saturated sodium chloride solution for 3-5 times, and then washed with deionized water for multiple times, and then the mixed solution is separated by a separatory funnel, and then the supernatant is separated by reduced pressure distillation using a rotary evaporator to obtain the compound described in formula (I);

[0029] The straight-chain alkyl acid is selected from one of decanoic acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, hexadecanoic acid, heptadecanoic acid, octadecanoic acid, nonadecanoic acid and eicosanoic acid.

[0030] According to some embodiments of the present application, the preparation of the compound of formula (II) comprises the following steps:

[0031] Malic acid and a linear alkyl primary alcohol are mixed in a molar ratio of 1:1, and then 1% by weight of p-toluenesulfonic acid and 0.5% by weight of toluene are added, and the reaction is carried out under nitrogen protection. The temperature of the oil bath is adjusted to 130° C., and the reaction is refluxed for 10 hours with continuous stirring. When the acid value of the reaction system reaches a stable state and no longer changes, the reaction product is taken out, washed with a saturated sodium chloride solution for 3-5 times, and then washed with deionized water for multiple times, and then the mixed solution is separated by a separatory funnel, and then the supernatant is separated by reduced pressure distillation using a rotary evaporator to obtain the compound described in formula (II);

[0032] Wherein, the straight-chain alkyl primary alcohol is selected from one of n-decanol, n-tridecanol, n-tetradecanol, n-pentadecanol, n-hexadecanol, n-heptadecanol, n-octadecyl alcohol, n-nonadecanol and n-eicosanol.

[0033] In a second aspect, the present application provides a method for preparing the above-mentioned high-strength PBS biodegradable plastic, which is achieved through the following technical solutions:

[0034] A method for preparing high-strength PBS biodegradable plastic comprises the following steps:

[0035] (1) Succinic acid, 1,4-butanediol, a second catalyst, and a first functional additive are uniformly mixed according to weight, and an esterification reaction is carried out at a pressure of 60-100 kPa and a temperature of 180-220° C. for 2-5 hours;

[0036] (2) adding the second functional auxiliary agent and the first catalyst into a reaction kettle under a protective gas atmosphere and stirring for 5-10 minutes to obtain a mixture;

[0037] (3) reducing the vacuum degree of the mixture to less than 200 Pa, raising the temperature to 230-250° C., carrying out polycondensation reaction for 3-6 hours, discharging the mixture under the protection of protective gas, and granulating the mixture to obtain high-strength PBS biodegradable plastic.

[0038] According to a method for preparing a high-strength PBS biodegradable plastic according to an embodiment of the present application, there are at least the following beneficial effects:

[0039] The PBS synthesized by the melt polycondensation method in the present application has uniform molecular weight distribution, stable structure, good physical and chemical properties, and is simple to operate, suitable for large-scale industrial production, and the molecular weight of the product is relatively high. On the one hand, during the melt polycondensation process, the raw material monomers and the generated polymers are both in a molten state, which is conducive to the full expansion and cross-linking of the molecular chains, thereby obtaining a high-quality PBS product. In addition, during the process of synthesizing PBS by the melt polycondensation method, the conversion rate of the raw materials is high, and the by-products are easy to remove, so the yield of the product is also relatively high, which helps to reduce production costs and improve economic benefits.

[0040] According to some embodiments of the present application, the protective gas in step (2) is selected from one of nitrogen, helium, neon, and argon, for example, the protective gas is nitrogen. Nitrogen is widely available and has low production costs. It can form an oxygen-free environment to prevent terminal hydroxyl groups from being oxidized and damaged, thereby reducing the occurrence of side reactions. Rare gases such as helium, neon, and argon are stable in nature and are not easily involved in chemical reactions, thereby reducing the generation of side reactions.

[0041] According to some embodiments of the present application, the stirring speed in step (2) is 2000-4000 r / min. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is the thermal analysis diagram of the high-strength PBS biodegradable plastic prepared in Example 1 of the present application.

[0043] Figure 2 This is the thermal analysis diagram of the high-strength PBS biodegradable plastic prepared in Comparative Example 1 of the present application.

[0044] Figure 3 This is a thermal analysis comparison diagram of the high-strength PBS biodegradable plastic prepared in Example 1 of the present application and Comparative Example 1. DETAILED DESCRIPTION

[0045] To make the purpose, technical solution and advantages of the present application clearer, the following will be further described in detail in conjunction with specific embodiments. The embodiments described here are only part of the embodiments of the present application and cannot be understood as limiting the scope of protection of the present application.

[0046] Example 1

[0047] Preparation of high-strength PBS biodegradable plastic: raw materials are selected according to weight: 4116 parts of succinic acid, 5022 parts of 1,4-butanediol, 4.116 parts of the first catalyst, 5 parts of the second catalyst; 8.058 parts of functional additives; wherein the functional additives include polyethylene wax and 2,3-dihydroxypropyl hexadecanoate in a weight ratio of 2.5:1; the first catalyst is tetrabutyl titanate; the second catalyst is tetramethyl dibutyl guanidine acetate;

[0048] (1) Succinic acid, 1,4-butanediol, a second catalyst, and polyethylene wax were uniformly mixed according to weight parts, and esterification reaction was carried out at a pressure of 80 kPa and a temperature of 200° C. for 4 hours;

[0049] (2) adding hexadecanoic acid 2,3-dihydroxypropyl ester and the first catalyst into a reaction kettle under a nitrogen protective gas atmosphere and stirring at a speed of 3000 r / min for 8 minutes to obtain a mixture;

[0050] (3) reducing the vacuum degree of the mixture to less than 200 Pa, raising the temperature to 240° C., carrying out polycondensation reaction for 5 hours, discharging the mixture under nitrogen protection, and granulating to obtain high-strength PBS biodegradable plastic;

[0051] Wherein, the preparation of 2,3-dihydroxypropyl hexadecanoate comprises the following steps:

[0052] Hexadecanoic acid and glycerol are mixed in a molar ratio of 1:1, and then 1% of p-toluenesulfonic acid by weight of the raw material and 0.5% of toluene with water by weight of the raw material are added, and the reaction is carried out under nitrogen protection. The temperature of the oil bath pot is adjusted to 130° C., and the reaction is refluxed for 10 hours with continuous stirring. When the acid value of the reaction system reaches stability and no longer changes, the reaction product is taken out, washed with a saturated sodium chloride solution for 3-5 times, and then washed with deionized water for multiple times, and then the mixed solution is separated by a separatory funnel, and then the supernatant is separated by reduced pressure distillation using a rotary evaporator to obtain hexadecanoic acid 2,3-dihydroxypropyl ester.

[0053] Example 2

[0054] Preparation of high-strength PBS biodegradable plastic: raw materials are selected according to weight: 5000 parts of succinic acid, 6000 parts of 1,4-butanediol, 0.9 parts of the first catalyst, 10 parts of the second catalyst; 550 parts of functional additives; wherein the functional additives include polypropylene wax and 2,3-dihydroxypropyl octadecanoate in a weight ratio of 2:1; the first catalyst is germanium dioxide; the second catalyst is hexabutylguanidine acetate;

[0055] (1) Succinic acid, 1,4-butanediol, a second catalyst, and polypropylene wax were uniformly mixed according to weight parts, and esterification reaction was carried out at a pressure of 100 kPa and a temperature of 180° C. for 2 hours;

[0056] (2) adding 2,3-dihydroxypropyl octadecanoate and the first catalyst into a reaction kettle under a nitrogen protective gas atmosphere and stirring at a speed of 4000 r / min for 5 minutes to obtain a mixture;

[0057] (3) reducing the vacuum degree of the mixture to less than 200 Pa, raising the temperature to 250° C., carrying out polycondensation reaction for 3 hours, discharging the mixture under nitrogen protection, and granulating the mixture to obtain high-strength PBS biodegradable plastic;

[0058] Wherein, the preparation of 2,3-dihydroxypropyl octadecanoate comprises the following steps:

[0059] Octadecanoic acid and glycerol are mixed in a molar ratio of 1:1, and then 1% by weight of p-toluenesulfonic acid and 0.5% by weight of toluene are added, and the reaction is carried out under nitrogen protection. The temperature of the oil bath is adjusted to 130° C., and the reaction is refluxed for 10 hours with continuous stirring. When the acid value of the reaction system reaches a stable state and no longer changes, the reaction product is taken out, washed with a saturated sodium chloride solution for 3-5 times, and then washed with deionized water for multiple times, and then the mixed solution is separated by a separatory funnel. Next, the supernatant is separated by reduced pressure distillation using a rotary evaporator to obtain octadecanoic acid 2,3-dihydroxypropyl ester.

[0060] Example 3

[0061] Preparation of high-strength PBS biodegradable plastic: raw materials are selected according to weight: 4000 parts of succinic acid, 5000 parts of 1,4-butanediol, 22 parts of the first catalyst, 1 part of the second catalyst; 4.5 parts of functional additives; wherein the functional additives include oxidized polyethylene wax and octadecyl malate in a weight ratio of 0.5:1; the first catalyst is tetrabutyl titanate; the second catalyst is trimethylamine;

[0062] (1) Succinic acid, 1,4-butanediol, a second catalyst, and oxidized polyethylene wax were uniformly mixed according to weight parts, and esterification reaction was carried out at a pressure of 60 kPa and a temperature of 220° C. for 5 hours;

[0063] (2) adding octadecyl malate and the first catalyst into a reaction kettle under a nitrogen protective gas atmosphere and stirring at a speed of 2000 r / min for 10 min to obtain a mixture;

[0064] (3) reducing the vacuum degree of the mixture to less than 200 Pa, raising the temperature to 230° C., carrying out polycondensation reaction for 6 hours, discharging the mixture under nitrogen protection, and granulating to obtain high-strength PBS biodegradable plastic;

[0065] Wherein, the preparation of n-octadecyl malate comprises the following steps:

[0066] Malic acid and n-octadecyl alcohol are mixed in a molar ratio of 1:1, and then 1% by weight of p-toluenesulfonic acid and 0.5% by weight of toluene are added, and the reaction is carried out under nitrogen protection. The temperature of the oil bath is adjusted to 130° C., and the reaction is refluxed for 10 hours with continuous stirring. When the acid value of the reaction system reaches a stable state and no longer changes, the reaction product is taken out, washed with a saturated sodium chloride solution for 3-5 times, and then washed with deionized water for multiple times, and then the mixed solution is separated by a separatory funnel, and then the supernatant is separated by reduced pressure distillation using a rotary evaporator to obtain n-octadecyl malate.

[0067] Example 4

[0068] Preparation of high-strength PBS biodegradable plastic: raw materials are selected according to weight: 4800 parts of succinic acid, 5800 parts of 1,4-butanediol, 6 parts of the first catalyst, 4 parts of the second catalyst; 100 parts of functional additives; wherein the functional additives include polyethylene wax and n-tetradecyl malate in a weight ratio of 3:1; the first catalyst is tetrabutyl titanate; the second catalyst is tetrahydropyridine;

[0069] (1) Succinic acid, 1,4-butanediol, a second catalyst, and polyethylene wax were uniformly mixed according to weight, and esterification reaction was carried out at a pressure of 90 kPa and a temperature of 210° C. for 3 hours;

[0070] (2) adding n-tetradecyl malate and the first catalyst into a reaction kettle under a nitrogen protective gas atmosphere and stirring at a speed of 3000 r / min for 7 min to obtain a mixture;

[0071] (3) reducing the vacuum degree of the mixture to less than 200 Pa, raising the temperature to 240° C., carrying out polycondensation reaction for 4 hours, discharging the mixture under nitrogen protection, and granulating to obtain high-strength PBS biodegradable plastic;

[0072] Wherein, the preparation of n-tetradecyl malate comprises the following steps:

[0073] Malic acid and n-tetradecanol are mixed in a molar ratio of 1:1, and then 1% by weight of p-toluenesulfonic acid and 0.5% by weight of toluene are added, and the reaction is carried out under nitrogen protection. The temperature of the oil bath is adjusted to 130° C., and the reaction is refluxed for 10 hours with continuous stirring. When the acid value of the reaction system reaches a stable state and no longer changes, the reaction product is taken out, washed with a saturated sodium chloride solution for 3-5 times, and then washed with deionized water for multiple times, and then the mixed solution is separated by a separatory funnel, and then the supernatant is separated by reduced pressure distillation using a rotary evaporator to obtain n-tetradecanol malate.

[0074] Comparative Example 1

[0075] Preparation of high-strength PBS biodegradable plastic: Select raw materials according to weight: 4116 parts of succinic acid, 5022 parts of 1,4-butanediol, 4.116 parts of the first catalyst, and 5 parts of the second catalyst; wherein the first catalyst is tetrabutyl titanate; the second catalyst is tetramethyl dibutyl guanidine acetate;

[0076] (1) Succinic acid, 1,4-butanediol, and a second catalyst were uniformly mixed according to weight, and esterification reaction was carried out at a pressure of 80 kPa and a temperature of 200° C. for 4 hours;

[0077] (2) adding the first catalyst into a reaction kettle under a nitrogen protective gas atmosphere and stirring at a speed of 3000 r / min for 8 min to obtain a mixture;

[0078] (3) The vacuum degree of the mixture is reduced to less than 200 Pa, the temperature is raised to 240° C., and the polycondensation reaction is carried out for 5 hours. The mixture is discharged under nitrogen protection and granulated to obtain high-strength PBS biodegradable plastic.

[0079] Comparative Example 2

[0080] Preparation of high-strength PBS biodegradable plastic: raw materials are selected according to weight: 4116 parts of succinic acid, 5022 parts of 1,4-butanediol, 4.116 parts of the first catalyst, 5 parts of the second catalyst; 8.058 parts of functional additives; wherein the functional additive is polyethylene wax; the first catalyst is tetrabutyl titanate; the second catalyst is tetramethyl dibutyl guanidine acetate;

[0081] (1) Succinic acid, 1,4-butanediol, a second catalyst, and polyethylene wax were uniformly mixed according to weight parts, and esterification reaction was carried out at a pressure of 80 kPa and a temperature of 200° C. for 4 hours;

[0082] (2) adding the first catalyst into a reaction kettle under a nitrogen protective gas atmosphere and stirring at a speed of 3000 r / min for 8 min to obtain a mixture;

[0083] (3) The vacuum degree of the mixture is reduced to less than 200 Pa, the temperature is raised to 240° C., and the polycondensation reaction is carried out for 5 hours. The mixture is discharged under nitrogen protection and granulated to obtain high-strength PBS biodegradable plastic.

[0084] Comparative Example 3

[0085] Preparation of high-strength PBS biodegradable plastic: raw materials are selected according to weight: 4116 parts of succinic acid, 5022 parts of 1,4-butanediol, 4.116 parts of the first catalyst, 5 parts of the second catalyst; 8.058 parts of functional additives; wherein the functional additive is 2,3-dihydroxypropyl hexadecanoate; the first catalyst is tetrabutyl titanate; the second catalyst is tetramethyl dibutyl guanidine acetate;

[0086] (1) Succinic acid, 1,4-butanediol, and a second catalyst were uniformly mixed according to weight, and esterification reaction was carried out at a pressure of 80 kPa and a temperature of 200° C. for 4 hours;

[0087] (2) adding hexadecanoic acid 2,3-dihydroxypropyl ester and the first catalyst into a reaction kettle under a nitrogen protective gas atmosphere and stirring at a speed of 3000 r / min for 8 minutes to obtain a mixture;

[0088] (3) reducing the vacuum degree of the mixture to less than 200 Pa, raising the temperature to 240° C., carrying out polycondensation reaction for 5 hours, discharging the mixture under nitrogen protection, and granulating to obtain high-strength PBS biodegradable plastic;

[0089] Wherein, the preparation of 2,3-dihydroxypropyl hexadecanoate comprises the following steps:

[0090] Hexadecanoic acid and glycerol are mixed in a molar ratio of 1:1, and then 1% of p-toluenesulfonic acid by weight of the raw material and 0.5% of toluene with water by weight of the raw material are added, and the reaction is carried out under nitrogen protection. The temperature of the oil bath pot is adjusted to 130° C., and the reaction is refluxed for 10 hours with continuous stirring. When the acid value of the reaction system reaches stability and no longer changes, the reaction product is taken out, washed with a saturated sodium chloride solution for 3-5 times, and then washed with deionized water for multiple times, and then the mixed solution is separated by a separatory funnel, and then the supernatant is separated by reduced pressure distillation using a rotary evaporator to obtain hexadecanoic acid 2,3-dihydroxypropyl ester.

[0091] Comparative Example 4

[0092] Preparation of high-strength PBS biodegradable plastic: raw materials are selected according to weight: 4116 parts of succinic acid, 5022 parts of 1,4-butanediol, 5 parts of the second catalyst; 8.058 parts of functional additives; wherein the functional additives include polyethylene wax and 2,3-dihydroxypropyl hexadecanoate in a weight ratio of 2.5:1; the second catalyst is tetramethyl dibutylguanidine acetate;

[0093] (1) Succinic acid, 1,4-butanediol, a second catalyst, and polyethylene wax were uniformly mixed according to weight parts, and esterification reaction was carried out at a pressure of 80 kPa and a temperature of 200° C. for 4 hours;

[0094] (2) adding hexadecanoic acid 2,3-dihydroxypropyl ester into a reaction kettle under a nitrogen protective gas atmosphere and stirring at a speed of 3000 r / min for 8 minutes to obtain a mixture;

[0095] (3) reducing the vacuum degree of the mixture to less than 200 Pa, raising the temperature to 240° C., carrying out polycondensation reaction for 5 hours, discharging the mixture under nitrogen protection, and granulating to obtain high-strength PBS biodegradable plastic;

[0096] Wherein, the preparation of 2,3-dihydroxypropyl hexadecanoate comprises the following steps:

[0097] Hexadecanoic acid and glycerol are mixed in a molar ratio of 1:1, and then 1% of p-toluenesulfonic acid by weight of the raw material and 0.5% of toluene with water by weight of the raw material are added, and the reaction is carried out under nitrogen protection. The temperature of the oil bath pot is adjusted to 130° C., and the reaction is refluxed for 10 hours with continuous stirring. When the acid value of the reaction system reaches stability and no longer changes, the reaction product is taken out, washed with a saturated sodium chloride solution for 3-5 times, and then washed with deionized water for multiple times, and then the mixed solution is separated by a separatory funnel, and then the supernatant is separated by reduced pressure distillation using a rotary evaporator to obtain hexadecanoic acid 2,3-dihydroxypropyl ester.

[0098] Experimental example

[0099] The high-strength PBS biodegradable plastics prepared in Examples 1-4 and Comparative Examples 1-4 were subjected to performance tests.

[0100] Test instrument: Differential Scanning Calorimeter (DSC).

[0101] Crystallization temperature and starting temperature test: non-isothermal crystallization, under nitrogen protection, one stage cooling, two stages heating, three stages heating: room temperature to 200℃, heating rate 10℃ / min, keep warm for 1min, then cool to room temperature, cooling rate 20℃ / min, keep warm for 1min, finally heat to 200℃, heating rate 10℃ / min, among which Figure 1 The thermal analysis of the high-strength PBS biodegradable plastic prepared in Example 1 corresponds to: Figure 2 The thermal analysis of the high-strength PBS biodegradable plastic prepared in Example 1 is shown in FIG. Figure 3 The thermal analysis is a comparison chart of the high-strength PBS biodegradable plastic prepared in Example 1 and Comparative Example 1.

[0102] Half-crystallization time test: under isothermal crystallization conditions and nitrogen protection, the room temperature was raised to 200°C, the heating rate was 10°C / min, the temperature was kept for 1 min, and the temperature was lowered to 92°C at a cooling rate of 50°C / min.

[0103] Crystallinity calculation: X C =ΔH m / ΔH 0 m , ΔH 0 m =102J / g.

[0104] Heat deformation temperature under load: Method B, refer to GB / T 1634.

[0105] Molding effect: Observe whether the ejector is deformed during demoulding. If not, it is qualified, otherwise it is unqualified.

[0106] The performance test data is shown in Table 1:

[0107] Table 1

[0108]

[0109] It can be seen from Table 1 that the high-strength PBS biodegradable plastics prepared in Examples 1-4 of the present application have high crystallization temperature, fast crystallization speed, and good heat deformation resistance.

[0110] The preparation raw materials of Comparative Example 1 do not contain functional additives, and the rest are the same as Example 1; the functional additive in the preparation raw materials of Comparative Example 2 is polyethylene wax, and does not contain 2,3-dihydroxypropyl hexadecanoate, and the rest are the same as Example 1; the functional additive in the preparation raw materials of Comparative Example 3 is 2,3-dihydroxypropyl hexadecanoate, and does not contain polyethylene wax, and the rest are the same as Example 1; the crystallization temperature, crystallization rate, and heat deformation resistance of the high-strength PBS biodegradable plastics prepared in Comparative Examples 1-3 are obviously not as good as those in Example 1 of the present application, and the molding effect is unqualified, indicating that the addition of specific types of functional additives to the preparation raw materials in the present application is very important for improving the crystallization temperature, crystallization rate and heat deformation resistance of PBS biodegradable plastics, and the additional long chain of polyethylene wax is matched with the long chain alkyl of the side chain of 2,3-dihydroxypropyl hexadecanoate, which increases the crystallization temperature of PBS plastic, accelerates the crystallization rate, has good processability, and at the same time improves the tensile strength and high temperature resistance of PBS plastic.

[0111] The preparation raw materials of Comparative Example 4 do not contain the first catalyst tetrabutyl titanate, and the rest are the same as Example 1. The crystallization temperature, crystallization speed, and heat deformation resistance of the high-strength PBS biodegradable plastic prepared in Comparative Example 4 are significantly inferior to those of Example 1 of the present application, and the molding effect is unqualified, indicating that tetrabutyl titanate exhibits higher catalytic activity in the synthesis of PBS, and the product has a larger molecular weight, which can improve the comprehensive performance of PBS biodegradable plastics.

[0112] The high-strength PBS biodegradable plastics prepared in Examples 1-4 and Comparative Examples 1-4 were tested for tensile strength and degradability, respectively, and the test methods were as follows:

[0113] The tensile strength is tested according to the standard of GB / T 1040-92.

[0114] The degradability is tested according to the standard GB / T 20197-2006, and the time required for the biodegradation rate to reach 60% is recorded as the degradability test data.

[0115] The test data is shown in Table 2 below:

[0116] Table 2

[0117]

[0118] It can be seen from Table 2 that the high-strength PBS biodegradable plastics prepared in Examples 1-4 of the present application have excellent tensile strength performance, while the degradation time is increased and have better durability.

[0119] In Comparative Examples 1-4, due to the different functional additives or catalysts, the tensile strength and degradation resistance of the prepared PBS biodegradable plastics decreased to varying degrees, indicating that the introduction of the long-chain alkyl group in the present application, the additional long chain of polyethylene wax and the side chain long-chain alkyl of 2,3-dihydroxypropyl hexadecanoate can improve the tensile strength of the PBS plastic, while improving the hydrophobicity of the PBS plastic, reducing the attachment of biological bacteria and the release of biodegradable enzymes, thereby extending the degradation time of the PBS plastic and making it more durable. The addition of the first catalyst tetrabutyl titanate can promote the branching and cross-linking of 2,3-dihydroxypropyl hexadecanoate in the enhanced polymerization process, thereby enhancing the tensile strength performance and degradation resistance of the PBS biodegradable plastic.

[0120] Although the embodiments of the present application have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions or variations may be made to the embodiments without departing from the principles and purpose of the present application, and that the technical solutions after these changes, modifications, substitutions or variations will fall within the scope of protection of the present application.

Claims

1. A high-strength PBS biodegradable plastic, characterized in that: The preparation comprises the following raw materials in parts by weight: 4000-5000 parts of succinic acid, 5000-6000 parts of 1,4-butanediol, 0.9-22 parts of the first catalyst, and 4.5-550 parts of a functional additive; Wherein, the functional auxiliary agent includes a first functional auxiliary agent and a second functional auxiliary agent; The first functional additive includes at least one of polyethylene wax, polypropylene wax, and oxidized polyethylene wax; The second functional auxiliary agent is selected from one of formula (I) or formula (II); In formula (I), n is a positive integer selected from 1 to 9; In formula (II), m is a positive integer selected from 1 to 9; The weight ratio of the first functional auxiliary agent to the second functional auxiliary agent is (0.5-3):

1.

2. A high-strength PBS biodegradable plastic according to claim 1, characterized in that: The weight ratio of the first functional auxiliary agent to the second functional auxiliary agent is (2-3):

1.

3. A high-strength PBS biodegradable plastic according to claim 1, characterized in that: The first catalyst includes at least one of a titanate catalyst and a germanium catalyst.

4. A high-strength PBS biodegradable plastic according to claim 3, characterized in that: The first catalyst includes at least one of tetrabutyl titanate and germanium dioxide.

5. A high-strength PBS biodegradable plastic according to claim 1, characterized in that: The preparation raw materials also include 1-10 parts by weight of a second catalyst; the second catalyst includes at least one of hexabutylguanidine acetate, tetramethyl dibutylguanidine acetate, trimethylamine, and tetrahydropyridine.

6. A high-strength PBS biodegradable plastic according to claim 1, characterized in that: The preparation of the compound of formula (I) comprises the following steps: A straight-chain alkyl acid and glycerol are mixed in a molar ratio of 1:1, and then 1% by weight of p-toluenesulfonic acid and 0.5% by weight of toluene are added, and the reaction is carried out under nitrogen protection. The temperature of the oil bath is adjusted to 130° C., and the reaction is refluxed for 10 hours with continuous stirring. When the acid value of the reaction system reaches a stable state and no longer changes, the reaction product is taken out, washed with a saturated sodium chloride solution for 3-5 times, and then washed with deionized water for multiple times, and then the mixed solution is separated by a separatory funnel, and then the supernatant is separated by reduced pressure distillation using a rotary evaporator to obtain the compound described in formula (I); The straight-chain alkyl acid is selected from one of decanoic acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, hexadecanoic acid, heptadecanoic acid, octadecanoic acid, nonadecanoic acid and eicosanoic acid.

7. A high-strength PBS biodegradable plastic according to claim 1, characterized in that: The preparation of the compound of formula (II) comprises the following steps: Malic acid and a linear alkyl primary alcohol are mixed in a molar ratio of 1:1, and then 1% by weight of p-toluenesulfonic acid and 0.5% by weight of toluene are added, and the reaction is carried out under nitrogen protection. The temperature of the oil bath is adjusted to 130° C., and the reaction is refluxed for 10 hours with continuous stirring. When the acid value of the reaction system reaches a stable state and no longer changes, the reaction product is taken out, washed with a saturated sodium chloride solution for 3-5 times, and then washed with deionized water for multiple times, and then the mixed solution is separated by a separatory funnel, and then the supernatant is separated by reduced pressure distillation using a rotary evaporator to obtain the compound described in formula (II); Wherein, the straight-chain alkyl primary alcohol is selected from one of n-decanol, n-tridecanol, n-tetradecanol, n-pentadecanol, n-hexadecanol, n-heptadecanol, n-octadecyl alcohol, n-nonadecanol and n-eicosanol.

8. A method for preparing a high-strength PBS biodegradable plastic according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Succinic acid, 1,4-butanediol, and the first functional auxiliary agent are uniformly mixed according to weight, and esterification reaction is carried out at a pressure of 60-100 kPa and a temperature of 180-220° C. for 2-5 hours; (2) adding the second functional auxiliary agent and the first catalyst into a reaction kettle under a protective gas atmosphere and stirring for 5-10 minutes to obtain a mixture; (3) reducing the vacuum degree of the mixture to less than 200 Pa, raising the temperature to 230-250° C., carrying out polycondensation reaction for 3-6 hours, discharging the mixture under the protection of protective gas, and granulating the mixture to obtain high-strength PBS biodegradable plastic; When the preparation raw material contains a second catalyst, the raw material added in step (1) also includes the second catalyst.

9. The method for preparing a high-strength PBS biodegradable plastic according to claim 8, characterized in that: The protective gas in step (2) is selected from one of nitrogen, helium, neon and argon.

10. The method for preparing a high-strength PBS biodegradable plastic according to claim 8, characterized in that: The stirring speed in step (2) is 2000-4000r / min.